KEMAMPUAN PENALARAN MATEMATIS SISWA DALAM MENYELESAIKAN SOAL LITERASI MATEMATIKA KONTEKSTUAL - Rajab Vebrian; Yudi Yunika Putra; Sari Saraswati; Tommy Tanu Wijaya (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
Mathematical literacy is essential because it can reason mathematically and formulate, apply, and interpret problem-solving in various everyday contexts. Following the PISA study, which assessed students aged 15 years with the age of high school students, this study aims to determine the reasoning ability of high school students in solving mathematical literacy problems. The method used in this research was descriptive qualitative. The research subjects were 22 students of class X, one of the private high schools in Pangkalpinang. Data collection techniques were written tests and interviews. The test instrument consisted of 10 items of developed mathematical literacy questions that meet the criteria of being valid, practical, and potentially affecting students' reasoning abilities. The questions were developed using the Bangka Belitung context. The students' answers were assessed based on a scoring rubric through primary mathematical skills of reasoning and argument indicators. Meanwhile, interviews were conducted with six students using the purposive sampling technique with high, medium, and low reasoning abilities. Interview data were used to dig deeper into students' reasoning abilities when solving the problem. Data were analyzed based on the percentage of students' mathematical reasoning abilities indicators, including data reduction, data presentation, and concluding/verification. The analysis results found that students' reasoning abilities mastery was very low on all indicators. At the indicator proposing allegations, mathematical manipulation, compiling evidence and reasons, it reaches a level of 42.88%, while at the level of mastery, the indicator concluded statements of 41.36%. The causes of students' difficulties in bringing up reasoning abilities included students who were not accustomed to solving questions that required high reasoning abilities. For example, mathematical literacy questions that were done and lack of mastery of mathematical concepts that had been studied made it challenging to bring up reasoning abilities.